Pathogenic de novo variants in PPP2R5C cause a neurodevelopmental disorder within the Houge-Janssens syndrome spectrum - Verbinnen, Iris; Douzgou Houge, Sofia; Hsieh, Tzung-Chien; Lesmann, Hellen; Kirchhoff, Aron; Geneviève, David; Brimble, Elise; Lenaerts, Lisa; Haesen, Dorien; Levy, Rebecca J.; Thevenon, Julien; Faivre, Laurence; et al. (The American journal of human genetics, 2025)
Pathogenic variants resulting in protein phosphatase 2A (PP2A) dysfunction result in mild to severe neurodevelopmental delay. PP2A is a trimer of a catalytic (C) subunit, scaffolding (A) subunit, and substrate binding/regulatory (B) subunit, encoded by 19 different genes. De novo missense variants in PPP2R5D (B56δ) or PPP2R1A (Aα) and de novo missense and loss-of-function variants in PPP2CA (Cα) lead to syndromes with overlapping phenotypic features, known as Houge-Janssens syndrome (HJS) types 1, 2, and 3, respectively. Here, we describe an additional condition in the HJS spectrum in 26 individuals with variants in PPP2R5C, encoding the regulatory B56γ subunit. Most changes were de novo and of the missense type. The clinical features were well within the HJS spectrum with strongest resemblance to HJS type 1, caused by B56δ variants. Common features were neurodevelopmental delay and hypotonia, with a high risk of epilepsy, behavioral problems, and mildly dysmorphic facial features. Head circumferences were above average or macrocephalic. The degree of intellectual disability was, on average, milder than in other HJS types. All variants affected either substrate binding (2/19), C-subunit binding (2/19), or both (15/19). Five variants were recurrent. Catalytic activity of the phosphatase was variably affected by the variants. Of note, PPP2R5C total loss-of-function variants could be inherited from a non-symptomatic parent. This implies that a dominant-negative mechanism on substrate dephosphorylation or general PP2A function is the most likely pathogenic mechanism.
Online verfügbar: 19. Februar 2025, Artikelversion: 6. März 2025
Gesehen am 09.09.2025